Tangible document sharing: handing over paper documents across a videoconferencing display - Tanaka, Kazuaki; Oshiro, Kentaro; Yamashita, Naomi; Nakanishi, Hideyuki (Frontiers in Robotics and AI, 2024)
Conventional techniques for sharing paper documents in teleconferencing tend to introduce two inconsistencies: 1) Media inconsistency: a paper document is converted into a digital image in the remote site; 2) Space inconsistency: a workspace deliberately inverts the partner's handwriting to make a document easy to read. In this paper, we present a novel system that eliminates these inconsistencies. The media and space inconsistencies are resolved by reproducing a real paper document on a remote site and allowing a user to hand the paper document over to a remote partner across a videoconferencing display. From a series of experiments, we found that reproducing a real paper document contributes to a higher sense of information sharing. We also found that handing over a document enhances a sense of space sharing regardless of whether the document is digital or paper-based. These findings provide insights into designing systems for sharing paper documents across distances. tabletop collaboration across distances, they still introduce some inconsistencies into the workspace, which limits natural interaction among remote users.In this paper, we focus on two inconsistencies that are commonly present in previous systems: 1) Media inconsistency: Many systems convert a paper document and a partner's handwritings into a digital image. This conversion produces an inconsistency between the media used for showing the document on local and remote sites. 2) Space inconsistency: Some systems deliberately turn the remote partner's handwriting upside down to make the document easy to read for the remote partner. However, these systems introduce an inconsistency between the interpersonal space and the shared workspace, which may deteriorate the users' feeling of working in the same space.